Adolescent Depressive Symptoms and Breakup Distress During Early Emerging Adulthood: Associations With the Quality of Romantic Interactions. (August 2017) - Shulman, Shmuel; Seiffge-Krenke, Inge; Scharf, Miri; Lev-Ari, Lilac; Levy, Gil
Breakups are a normative and frequent part of the romantic experience. In this longitudinal study, we followed 144 adolescents (mean age = 16.57) for a period of 4 years and examined the extent to which level of depressive symptoms predicts the intensity of breakup distress during emerging adulthood and, further, the extent to which breakup distress reported during emerging adulthood is associated with the quality of a current romantic relationship. The findings suggest that higher levels of depressive symptoms during adolescence can lead to more difficulty in recovering from breakup in early emerging adulthood. In addition, experiencing greater breakup distress during emerging adulthood was associated with greater difficulty in handling a current romantic relationship. This association was, however, found only among women. The gender distinctive reaction to breakup distress among emerging adults is discussed.